2018
DOI: 10.1038/s41379-018-0019-5
|View full text |Cite
|
Sign up to set email alerts
|

Presence of high-endothelial venules correlates with a favorable immune microenvironment in oral squamous cell carcinoma

Abstract: Oral squamous cell carcinomas are associated with a poor prognosis, which may be partly due to functional impairment of the immune response. Lymphocyte recruitment to the tumor site is facilitated by high-endothelial venules, whereas expression of programmed-death ligand 1 (PD-L1) can impair T-cell function. Thus, we hypothesize that these factors are important in shaping the immune response in oral squamous cell carcinoma. In the present study, we characterized the immune infiltrate in formalin-fixed, paraffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 61 publications
5
80
2
Order By: Relevance
“…Macrophages were the most commonly studied cells of those addressed in this review [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (Table 1), and the majority of the studies reported a negative effect on survival of this cell type. A few studies scored macrophages infiltrating the tumour islands and the tumour-stroma separately and found that the effect on survival differed between the compartments.…”
Section: Cd163+ Macrophages and Cd57+ Nk Cells Have Prognostic Potentialmentioning
confidence: 99%
See 3 more Smart Citations
“…Macrophages were the most commonly studied cells of those addressed in this review [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (Table 1), and the majority of the studies reported a negative effect on survival of this cell type. A few studies scored macrophages infiltrating the tumour islands and the tumour-stroma separately and found that the effect on survival differed between the compartments.…”
Section: Cd163+ Macrophages and Cd57+ Nk Cells Have Prognostic Potentialmentioning
confidence: 99%
“…Thirteen different studies assessed various subsets of T cells 23,28,29,34,40,[44][45][46][47][48][49][50][51] (Table 3). High numbers of tumourinfiltrating CD3+ T cells (pan T cell marker), CD4+ T cells (T helper (Th) cell marker) or CD8+ T cells (T cytotoxic (Tcyt) marker) were usually associated with somewhat longer survival, whereas high numbers of forkhead box P3 (FOXP3)+ T-regulatory cells showed significant association with decreased survival in two of the five studies addressing this cell type.…”
Section: T Cells B Cells DC and Mast Cells Lack Evidence Of Prognosmentioning
confidence: 99%
See 2 more Smart Citations
“…TLS density is associated with higher numbers of CD8+ and CD4+ T-cells in tumors [76], and evidence indicates that TLSs play a major role in controlling tumor invasion and metastasis. A positive impact of TLS density on OS and disease-free survival in lung cancer [71,[76][77][78], colorectal cancer [79,80], pancreatic cancer [81,82], oral squamous cell carcinoma [83], and invasive breast cancer [70,[84][85][86] has been documented. Importantly, its prognostic value is independent of tumor-node-metastasis (TNM) staging in most malignancies, suggesting TLS can induce a systemic, long-lasting anti-tumor response.…”
Section: Tertiary Lymphoid Structures In Solid Tumors and Mpm: Where mentioning
confidence: 99%